KEMAMPUAN MENULIS SURAT RESMI SEKRETARIS HIMPUNAN MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA UNIVERSITAS RIAU - Hesti Handayani S Handayani S; Hasnah Faizah; Charlina ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Writing skills is to measure the level of skills in writing a formal letter in the form of numbers written by the secretary of the Student Association of Language Study Program and Literature Indonesia Riau University. This study aimed to describe the ability to write a formal letter to the Student Association of Educational Studies Language and Literature Indonesia. The method used in this research is descriptive method and qualitative types. The data source of this research were 75 letters taken from the Student Association of Educational Studies Program Language and Literature Indonesia Riau University. The samples taken are 37 letters. The results of the analysis conducted that an official letter that was made by the Student Association Language Study Program and Literature Indonesia has 10 parts, namely, letterhead, dated letters, numbers, attachment, and the case or subject, destination address, salutation, letter, greeting cover , maker name letters, signatures. Component or part of this official letter plus an indicator of language (the language of the letter). Official Letter Writing Ability Secretary of the Student Association of Language Study Program and Literature Indonesia Riau University, relatively high rate capability with the average value of 86.80%. High-ability level amounted to 15 samples are samples 1, 5, 7, 8, 14, 16, 21, 22, 27, 28, 32, 33, 34, 35, and 37, and the rest of the level capable of being that is numbered 22 samples. Total average value (1) letterhead is 3.00, (2) the date of the letter amounted to 2,62, (3) number, p / subject, attachments (if any) that the average value of 2.05, ( 4) addressee average value amounted to 2.94, (5) greeting is 2.35, (6) the contents of the letter (clarity) with an average value of 4.00, and (spelling) accounted average value ratanya namely 3.46, (7) greeting cover its average value amounted to 2.00, while, (8) the name of the manufacturer's letter also amounts to the average value of the same, namely 2.00, (9) the signature average value namely 2.00, and (10) the language of letters with the average value amounted to 3.94.